Linguistic Signs On Megalithic Stone Meaning In Gomo South Nias District - Amelia Yuli Astuti; Semberiyanto Tafonao (Jurnal Ilmiah Langue and Parole, 2023)
This research is entitled linguistic signs on meaning of megalithic stones in Orahili Gomo, South Nias. It explains the sign of the linguistic meaning of the signifier and the signified, the denotative meaning and connotative meaning of megalithic stone. It aims to describe the sequence of signifier and signified and describe the denotative and connotative meaning of megalithic stone. Based on these sources, the data were collected using the observation method and photo techniques. The analysis is carried out with semiotics, the sign of linguistic meaning and the order of the signifier method. The data were analyzed by relating it to the concept proposed by Saussure (2011) and Chandler (2002). Saussure theory is to classify signifier and signified. Chandler theory is to classify denotative and connotative meanings. Result the analysis is presented descriptively. After analyzing the data, it was found there are several specifications of the meaning of megalithic stone. This study shows that megalithic stones have high cultural significance and value, especially in Orahili Gomo. Megalithic stones have the form of signifier and signified and the meaning we can see from the shape and size of megalithic stones.